2020
DOI: 10.12688/f1000research.23635.2
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific mitochondrial gene variation can be as low as that of nuclear rRNA

Abstract: Background: Mitochondrial DNA (mtDNA) has long been used to date historical demographic events. The idea that it is useful for molecular dating rests on the premise that its evolution is neutral. Even though this idea has long been challenged, the evidence against clock-like evolution of mtDNA is often ignored. Here, we present a particularly clear and simple example to illustrate the implications of violations of the assumption of selective neutrality. Methods: DNA sequences were generated for the mtDNA COI g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…While single-locus data has its limitations in making inferences about historical demography (Matumba et al 2020), DNA barcoding, or the use of other single-locus DNA markers has provided tremendous insight into identifying evolutionary significant units and providing information on species in further need of exploration (Sholihah et al 2020;Wang et al 2020;Nneji et al 2020;Bousjein et al 2021;León-Tapia 2021). These data are particularly helpful when aiming to explore broad-scale patterns such as those on a continental scale (Dinça et al 2021) or across species (Doorenweerd et al 2020), especially for a large number of taxonomic groups, as demonstrated here.…”
Section: Discussionmentioning
confidence: 99%
“…While single-locus data has its limitations in making inferences about historical demography (Matumba et al 2020), DNA barcoding, or the use of other single-locus DNA markers has provided tremendous insight into identifying evolutionary significant units and providing information on species in further need of exploration (Sholihah et al 2020;Wang et al 2020;Nneji et al 2020;Bousjein et al 2021;León-Tapia 2021). These data are particularly helpful when aiming to explore broad-scale patterns such as those on a continental scale (Dinça et al 2021) or across species (Doorenweerd et al 2020), especially for a large number of taxonomic groups, as demonstrated here.…”
Section: Discussionmentioning
confidence: 99%
“…While single-locus data has its limitations in making inferences about historical demography (Matumba et al, 2020), DNA barcoding, or the use of other single-locus DNA markers, has provided tremendous insight into identifying evolutionary significant units and providing information on species in further need of exploration (Bousjein et al, 2021;León-Tapia, 2021;Nneji et al, 2020;Sholihah et al, 2020;Wang et al, 2020). These data are particularly helpful when aiming to explore broad-scale patterns such as those on a continental scale (Dincă et al, 2021) or across species (Doorenweerd et al, 2020), especially for a large number of taxonomic groups, as demonstrated here.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…Mitochondrial DNA tends to be under strong selection pressure (Ballard & Kreitman, 1995; Matumba et al, 2020), thus violating the assumption of the neutral theory of evolution (Kimura, 1983) and affecting divergence time estimation (Stewart et al, 2008; Matumba et al, 2020). No mitogenome sequence is yet available for S. compressa .…”
Section: Methodsmentioning
confidence: 99%